Cooperation and competition among primitive peoples (McGraw-Hill publications in sociology, ,, 1976)
Description Not Provided
Preface / Margaret Mead , Introduction / Margaret Mead , The Arapesh of New Guinea / Margaret Mead , The Eskimo of Greenland / Jeannette Mirsky , The Ojibwa of Canada / Ruth Landes , The Bachiga of East Africa / May M. Edel , The Ifugao of the Philippine Islands / I. Goldman , The Kwakiutl of Vancouver Island / I. Goldman , The Manus of the Admiralty Islands / Margaret Mead , The Iroquois / B. Quain , The Samoans / Margaret Mead , The Zuni of New Mexico / I. Goldman , The Bathonga of South Africa / I. Goldman , The Dakota / Jeannette Mirsky , The Maori of New Zealand / B. Mishkin , Interpretative statement / Margaret Mead.